2010
DOI: 10.3346/jkms.2010.25.6.824
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G Subclass Deficiency is the Major Phenotype of Primary Immunodeficiency in a Korean Adult Cohort

Abstract: Primary immunodeficiency disease (PID) is a rare disorder in adults. Most often, serious forms are detected during infancy or childhood. However, mild forms of PID may not be diagnosed until later in life, and some types of humoral immunodeficiency may occur in adulthood. The purpose of this study was to identify clinical features of PID in Korean adults. A retrospective study was performed on 55 adult patients who were diagnosed as PID between January 1998 and January 2009 at a single tertiary medical center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…To the best of our knowledge, there have been few nationwide surveys of PID in an adult population in Korea, except one study reporting a PID prevalence of 1.13 per 100,000 in a pediatric population [1]. Although the reason the prevalence of PID is higher in adult asthmatics than in the general populations is not fully understood, it is conceivable that asthma is the most common comorbid condition in an adult PID cohort in Korea [4]; asthmatics with PID (especially IgG 3 SCD) suffered from recurrent respiratory infections, contributing to asthma exacerbation and asthma severity. Therefore, asthmatics with PID can be detected more frequently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there have been few nationwide surveys of PID in an adult population in Korea, except one study reporting a PID prevalence of 1.13 per 100,000 in a pediatric population [1]. Although the reason the prevalence of PID is higher in adult asthmatics than in the general populations is not fully understood, it is conceivable that asthma is the most common comorbid condition in an adult PID cohort in Korea [4]; asthmatics with PID (especially IgG 3 SCD) suffered from recurrent respiratory infections, contributing to asthma exacerbation and asthma severity. Therefore, asthmatics with PID can be detected more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these repiratoty infections are known as major triggering factors for asthma exacerbation in adult asthmatics [3]. Recently, we demonstrated that immunoglobulin G 3 (IgG 3 ) subclass deficiency (IgG 3 SCD) is the most common type of PID associated with asthma exacerbation in adult asthmatics [4], in which monthly intravenous immunoglobulin (IVIG) therapy was beneficial for preventing asthma exacerbation [5]. We hypothesized that PID is associated with frequent asthma exacerbations and severe asthma in adult asthmatics.…”
Section: Introductionmentioning
confidence: 99%
“…IgG 3 subclass deficiency is closely associated with recurrent upper and lower respiratory infections, particularly in patients with respiratory allergy [18,19]. IgG3 is the predominant subclass involved in primary immune response to viral antigens, to M. Catarrhalis and S. pyogenes [20,21], as well as atypical pathogen infections and the exacerbations of asthma symptoms [19].…”
Section: Discussionmentioning
confidence: 99%
“…IgG3 is the predominant subclass involved in primary immune response to viral antigens, to M. Catarrhalis and S. pyogenes [20,21], as well as atypical pathogen infections and the exacerbations of asthma symptoms [19]. We did not find IgG3 deficiency, but the statistically significant increase after allergen immunotherapy could support several clinical findings that patients after such treatment better tolerate respiratory infections, not only due to suppression of allergic Th2 inflammation, but also due to changes in immune regulation (increased ROS in leukocytes, increased IgG3).…”
Section: Discussionmentioning
confidence: 99%
“…Other disorders with IgG4 deficiency are Down syndrome, immune thrombocytopenia, lupus erythematosus, and growth hormone deficiency. Monthly intravenous immunoglobulins (IVIG) are the mainstay of treatment for symptomatic patients with IgG subclass deficiencies (9,10) . There are scant data on abnormal Ig subclasses in women with RM (11) .…”
Section: Introductionmentioning
confidence: 99%